The two cultures: an overview. - Syed Alwi Shahab, (Universiti Kebangsaan Malaysia, 1974)
The writer discusses several writers' opinions concerning the crystalization of two cultures as a result of the recent development of science and technology, which had separated two groups of people in the society hardly understand each other, i.e. the scientists and technologists on the other hand and literary men and artists on the other. Arguments of both sided are also discussed.